A Cross-Sectional Study on the relation between Teachers' Organizational Commitment to Change and their Acceptance and Use of an LMS in the UAE Applied Technology High Schools - Ayoub, Shadi (2016)
The importance of Learning Management Systems (LMSs) in teaching motivates schools to adopt them. Teachers' ongoing contribution and participation are key in order to realize the value from these systems. However, limited research explains secondary school teachers’ acceptance and use of an LMS worldwide in general and in UAE in particular. It is important to understand the many emotional and behavioural aspects pertaining to teachers’ technology acceptance and their relationship with other factors situated within the school organisation. Many factors were identified that, directly or indirectly, affect teachers' acceptance and use of technology. Another domain that the study used is teachers’ organisational commitment, which is considered very important as it directly relates to many areas in education such as teaching and learning, well-being, and school success. Different key forms of teacher commitment have been identified in research including commitment to the organisation, commitment to student learning, and commitment to the profession. Teacher commitment, in all forms, has been used as an important factor to determine teachers' outcomes. Building on the ideas mentioned above, the study examined relationships among measures of UAE secondary school teachers’ acceptance and use of an LMS and their organisational commitment profile. Three widely cited theoretical models were used namely, the Unified Theory of Acceptance and Use of Technology (UTAUT), the Theory of Reasoned Action (TRA), and the Three-Component Model of Organizational Commitment (TCM). The study used TCM to generate the organizational commitment profiles for teachers assuming a change context due to introducing a new technology. The Latent Profile Analysis (LPA) method was used to generate the teachers’ commitment profiles. The commitment profile was used as a group moderator to assess its effect on technology acceptance, measured as behavioural intention (BI), self-reported use (SRU), and observed frequency of use (FRQ). Commitment profile was also used as a moderator of the different relationships between predictors and BI. Other moderators were also included such as gender, perceived mandatoriness, LMS user type, work experience, and organizational tenure. A total 311 high school teachers from seven schools completed a survey questionnaire. In addition, real usage log data extracted from the system was used to observe actual use of the LMS (FRQ) and to group teachers based on their usage level. The study first investigated which factors affected teachers’ acceptance of the LMS by applying multiple regression analysis using Ordinary Least Square (OLS) method side-by-side with Partial Least Squares (PLS) model. The main predictors of LMS acceptance were: attitude towards using the LMS (ATT), performance expectancy (PE), social influence (SI) and facilitating conditions (FC). Effort expectancy (EE) was of little importance. The observed use of the LMS was significantly predicted by SRU. Then the study tested different moderation effects and found that gender is a significant moderator of the relationship between PE and BI while user type was a strong moderator of the association between FC and SRU. On the other hand, perceived mandatoriness and age were found to be insignificant moderators. Teachers with different organizational commitment profiles were found to have varying levels of BI and SRU. On the other hand, varying commitment profiles did not report different levels of FRQ. Lastly, the study reported marginal effect of the commitment profile as a moderator when interacted with other factors such as gender, perceived mandatoriness, user type, and work experience. The overall findings in UAE context has implications for theory and practice.